Evaluation of in vitro activity of ceftolozane/tazobactam and comparators against recent clinical bacterial isolates, and genomics of Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli isolates that demonstrated resistance to ceftolozane/tazobactam: data from Kuwait and Oman. Issue 2 (21st April 2022) - Alfouzan, Wadha; Dhar, Rita; Mohsin, Jalila; Khamis, Feryal; Mokaddas, Eiman; Abdullah, Abrar; Mustafa, Abu Salim; Otero, Aurelio; Wanis, Paulette; Matar, Samar Hussien; Khalil, Sherif; Alekseeva, Irina; et al.
Abstract: Background: The treatment options for infections caused by MDR Gram-negative bacteria have been limited, especially for infections caused by bacteria that produce carbapenemases and/or ESBLs. Ceftolozane/tazobactam is a cephalosporin/β-lactamase inhibitor developed to treat Gram-negative bacteria. Methods: Ceftolozane/tazobactam and 14 comparators (amikacin, aztreonam, cefepime, cefotaxime, cefoxitin, ceftazidime, ceftriaxone, ciprofloxacin, colistin, ertapenem, imipenem, levofloxacin, meropenem and piperacillin/tazobactam) were evaluated against Pseudomonas aeruginosa and Enterobacterales isolates collected from Kuwait and Oman ( n = 606) during 2016–17. In addition, further analysis of resistance mechanisms to ceftolozane/tazobactam was done utilizing WGS. Non-susceptible isolates from ceftolozane/tazobactam surveillance were selected for analysis. Overall, 35 strains underwent WGS. Results: Among isolates from Kuwait, susceptibility of P. aeruginosa, Escherichia coli and Klebsiella pneumoniae to ceftolozane/tazobactam was 79.8%, 95.7% and 87.5%, respectively, and from Oman was 92.3%, 93.1% and 88.5%, respectively. No P. aeruginosa with a ceftolozane/tazobactam MIC <32 mg/L encoded β-lactamases besides normal chromosomal enzymes (PDC variants or OXA-50-like) whereas all but one P. aeruginosa isolate with MIC >32 mg/L encoded either MBLs (60%), VEB-1 (19%) or additional OXAs (3.7%). Conclusions: Colistin followed by ceftolozane/tazobactam showed the greatest activity against P. aeruginosa . Enterobacterales showed more susceptibility to ceftolozane/tazobactam than to piperacillin/tazobactam, but meropenem and colistin showed better activity.